Welfare and Poverty Effects of Global Agricultural and Trade Policies Using the Linkage Model - Anderson, Kym; Valenzuela, Ernesto; van der Mensbrugghe, Dominique (World Bank, Washington, DC, 2017)
This paper analyzes the economic effects of agricultural price and merchandise trade policies around the world as of 2004 on global markets, net farm incomes, and national and regional economic welfare and poverty, using the global economy wide Linkage model, new estimates of agricultural price distortions for developing countries, and poverty elasticity's approach. It addresses two questions: to what extent are policies as of 2004 still reducing rewards from farming in developing countries and thereby adding to inequality across countries in farm household incomes? Are they depressing value added more in primary agriculture than in the rest of the economy of developing countries, and earnings of unskilled workers more than of owners of other factors of production, thereby potentially contributing to inequality and poverty within developing countries (given that farm incomes are well below non-farm incomes in most developing countries and that agriculture there is intensive in the use of unskilled labor)? Results are presented for the key countries and regions of the world and for the world as a whole. They reveal that, by moving to free markets, income inequality between countries will be reduced at least slightly, all but one-sixth of the gains to developing countries will come from agricultural policy reform, unskilled workers in developing countries the majority of whom work on farms will benefit most from reform, net farm incomes in developing countries will rise by 6 percent compared with 2 percent for non-agricultural value added, and the number of people surviving on less than US$1 a day will drop 3 percent globally.